Efektivitas Buku Saku Fisika Berbasis Problem Based Learning (PBL) terhadap Hasil Belajar Siswa - Reta Reta; Ahmad Amin; Ovilia Putri Utami Gumay (SPEJ (Science and Physic Education Journal), 2022)
Abstract: This study aimed to determine the quality of developing a physics pocketbook based on Problem Based Learning on elasticity and Hooke's law in terms of effectiveness. This research is the research and development of R&D (Research and Development) using the 4D development model, which has a development stage consisting of 4 sets of action, namely: Define, Design, Development, and Dissemination. . Data collection techniques in the form of tests. The subjects of this research were class XI students of SMA Negeri Surulangun. The results showed that the effectiveness assessment obtained count = 9.35 and table = 2.052 with an average score obtained by students of 24.78 after using the Problem Based Learning-based physics pocketbook, the students' physics learning outcomes significantly increased or were effective. In conclusion, the bag based on Problem Based Learning is already practical, so that this pocketbook can be used in learning. Keywords: Elasticity and Hooke's Law, Development, Problem Based Learning